THE EU PRIVATE INTERNATIONAL LAW FRAMEWORK FOR THE ACKNOWLEDGMENT AND EXECUTION OF JUDGEMENTS IN EMPLOYMENT MATTERS: Received: 18th March 2023; Revised: 28th March 2023, 06th July 2023; Accepted: 14th July 2023 - Vorpsi, Laura Çami; Skënderi, Xhon (PEOPLE: International Journal of Social Sciences, 2023)
This study seeks to examine the recognition and enforcement of EU employment judgements under private international law (PIL). The objectives are to examine the legal framework regulating the recognition and enforceability of employment decisions and to assess the influence of Brexit on EU-UK employment-related rulings. The methodology includes a comprehensive review of applicable EU legislation, case law, and employment-related regulations. This will reveal the conditions for recognising and enforcing employment decisions, the function of the EU Regulation on jurisdiction and judgements, and the scope of the EU Directive on judgement enforcement. The findings will elucidate the complexities and difficulties of PIL in employment matters, including the implications of Brexit. They will promote legal certainty and safeguard employee rights in the EU. Policymakers, legal practitioners, and stakeholders in cross-border employment disputes will gain valuable insights. Based on the results of future research, legal framework reforms may be proposed. Comparative studies of PIL frameworks in other jurisdictions could contribute to the expansion of employment law knowledge internationally.